Reading Václav Havel - Danaher, David S. (Book collections on Project MUSE., 2015)
In Reading Václav Havel, David S. Danaher approaches Havel's remarkable body of work holistically, focusing on the language, images, and ideas which appear and reappear in the many genres in which Havel wrote.